A Case Report of a Patient Involved in an Alleged Homicide–Attempted Suicide Case - a Theoretical Discussion on the Theory of Homicide-Suicide - Ahmad Nabil MR,; Suarn S, (Penerbit UKM, 2015)
This case report stresses the role of depression in the manifestation of a homicide-attempted suicide. We report the case of a man who allegedly murdered his partner and then attempted suicide. Previously, he had several failures and rejections in relationships in addition to work-related stress. He was diagnosed with major depressive disorder and treated with antidepressant. The scarcity of homicide-attempted suicide as exemplified in this case could give an insight to the Psychiatrist for better understanding and possible prevention.